Expanding the genetic architecture of nicotine dependence and its shared genetics with multiple traits - Bryan C. Quach (Nature Portfolio, 2020)
There is strong genetic evidence for cigarette smoking behaviors, yet little is known on nicotine dependence (ND). Here, the authors perform a genome-wide association study on ND in 58,000 smokers, identifying five genome-wide significant loci.